PRIVACY PRESERVING SEARCH OVER ENCRYPTED DATA OF MULTIPLE DATA OWNER - Aditya R. Jadhav; Prasad Deshpande.; SachinWalunj. (International Journal of Innovations in Engineering Research and Technology, 2021)
The advent of cloud computing, data owners are driven to uploads their complicated information management systems from native sites to business public cloud for excellent flexibility and economic savings. Except protective information privacy, sensitive information must be encrypted before uploading, that obsoletes ancient information utilization supported plain text keyword search. Thus, enabling anencrypted cloud information search service is of overriding importance. Considering the massive variety of information users and documents in cloud, it’s necessary for the search service to permit multi-keyword question and supply result similarity ranking to satisfy the eective information retrieval would they like. Related works on searchable encoding concentrate on single keyword search or Boolean keyword search, and barely differentiate the search results. During this paper, for the first time, we have a tendency to done and solve the difficult downside of privacy preserving multi-keyword ranked search over encrypted cloud information (PSEM), and establishes a collection of strict privacy needs for such a secure cloud information utilization system to become a reality.